Simulation of V2X communications - Zeng, Yuwei (2016)
The emerging vehicle-to-vehicle and vehicle-to-infrastructure (V2X) communication enables a new way to create a safer, more comfortable and environmental friendly traffic system. The Green Light Optimized Speed Advisory(GLOSA) application is one of such applications. Using real-time traffic data from V2X communication, it ensures vehicle passing an intersection during the green (and amber) light period and minimizes the stop delay through speed control. A GLOSA algorithm is designed and evaluated in this project. The simulations are implemented under an integrated environment, where the traffic simulator VISSIM and application simulator Matlab are synchronized and bilaterally communicate with each other through the COM interface. Comparing to the existing researches, this GLOSA algorithm is able to calculate a suggested speed interval for every vehicle once detected without cycle, distance or queue length limits, and it sets the maximum legal speed within this interval to vehicles to maximize the traffic efficiency. More importantly, using the exponential queue discharge model proposed by R. Akçelik, M. Besley, it takes the existing queue on road and driver's response time into consideration and provides a more precise calculation. The GLOSA algorithm proved to be effective during the simulation. It eliminated the queue length up to 100%, and reduced up to 25% in fuel consumption and CO emission. The project also further evaluated the GLOSA performance with different penetration rates, working ranges and activation frequencies for more universe application. It is found that the higher penetration rate is, the less the queue length, stop delay, fuel consumption and CO emission are. The minimum GLOSA working range is found to be linearly correlated with its activation frequency, but once it exceeds the minimum working range, the activation frequency does not affect GLOSA performance.